Caffeic Acid in Tobacco Root Exudate Defends Tobacco Plants From Infection by Ralstonia solanacearum - Li, Shili; Pi, Jing; Zhu, Hongjiang; Yang, Liang; Zhang, Xingguo; Ding, Wei (Frontiers in Plant Science, 2021)
In rhizospheres, chemical barrier-forming natural compounds play a key role in preventing pathogenic bacteria from infecting the plant roots. Here, we sought to identify specific phenolic exudates in tobacco (Nicotiana tobaccum) plants infected by the soil-borne pathogen Ralstonia solanacearum that may exhibit antibacterial activity and benefit plant resistance against pathogens. Among the detected phenolic acids, only caffeic acid was significantly induced in infected plants by R. solanacearum relative to healthy plants, and the concentration of caffeic acid reached 1.95 μg/mL. In vivo, caffeic acid at 200 μg/mL was highly active against R. solanacearum and obviously damaged the membrane structure of the R. solanacearum cells, resulting in the thinning of the cell membrane and irregular cavities in cells. Moreover, caffeic acid significantly inhibited biofilm formation by repressing the expression of the lecM and epsE genes. In vitro, caffeic acid could effectively activate phenylalanine ammonia-lyase (PAL) and peroxidase (POD) and promote the accumulation of lignin and hydroxyproline. In pot and field experiments, exogenous applications of caffeic acid significantly reduced and delayed the incidence of tobacco bacterial wilt. Taken together, all these results suggest that caffeic acid played a crucial role in defending against R. solanacearum infection and was a potential and effective antibacterial agent for controlling bacterial wilt.